2003
DOI: 10.1034/j.1601-5223.2003.01717.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosomes pairing in two Arvicolidae species: Microtus nivalis and Arvicola sapidus

Abstract: Arvicolid rodents present both synaptic and asynaptic sex chromosomes. We analyzed the pairing behaviour of sex chromosomes in two species belonging to this rodent group (Microtus nivalis and Arvicola sapidus). At pachynema, the sex chromosomes of both species paired in a small region while the rest remain unsynapsed. Consequently at metaphase I, sex chromosomes present end-to-end association. Thus, the pairing behaviour of sex chromosomes in these species is very similar to that previously described for other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…The pairing between sex chromosomes is restricted to very short terminally located heterochromatic segments of the neo-X and neo-Y. Similar meiotic behaviour of sex chromosomes is reported in species of Arvicolidae (Megías-Nogales et al, 2003). These mechanisms result in the appearence of loop-like or "parachute"-like associations of sex chromosomes, typical of Coleoptera (e.g.…”
Section: Structure and Evolution Of The Neo-xymentioning
confidence: 62%
“…The pairing between sex chromosomes is restricted to very short terminally located heterochromatic segments of the neo-X and neo-Y. Similar meiotic behaviour of sex chromosomes is reported in species of Arvicolidae (Megías-Nogales et al, 2003). These mechanisms result in the appearence of loop-like or "parachute"-like associations of sex chromosomes, typical of Coleoptera (e.g.…”
Section: Structure and Evolution Of The Neo-xymentioning
confidence: 62%
“…Furthermore, non-recombining status is extended to the whole Y chromosome in some of the species analysed (M. cabrerae, M. arvalis, M. agrestis, M. guentheri), since they present asynaptic sex chromosomes (Megı´as-Nogales et al 2003). In fact, this ampli¢cation mechanism is not valid for the heterochromatic blocks of both X and Y chromosomes in Microtus because these regions never pair at meiosis, whatever the condition, synaptic or asynaptic, of the sex chromosomes (Singh et al 2000, Meg as-Nogales et al 2003.…”
Section: Resultsmentioning
confidence: 99%
“…One of them stated that large heterochromatic regions on sex chromosomes could interfere with synapsis (Solari and Ashley, 1977). However, asynapsis also occurs in species without heterochromatic regions on sex chromosomes (Ashley et al, 1989;Carnero et al, 1991;Borodin et al, 1995;Megías-Nogales et al, 2003). Also, the loss or malfunction of the pairing regions in sex chromosomes has been proposed as the cause of asynapsis Jiménez et al, 1991).…”
Section: Synaptic and Asynaptic Sex Chromosomesmentioning
confidence: 99%
“…The alternative to this hypothesis is the existence of a common origin for the species with asynaptic sex chromosomes. Megías-Nogales et al (2003) have suggested that asynaptic sex chromosomes originated only once in the ancestral species of the lineage that gave rise to the M. arvalis/agrestis group of species, while in the rest of Microtus species the ancestral synaptic condition remained.…”
Section: Synaptic and Asynaptic Sex Chromosomesmentioning
confidence: 99%
See 1 more Smart Citation